DYNAMIC ASSESSMENT METHODS IN A CHANGING WORLD - TULBURE, Ildiko (Studia Universitatis Babeș-Bolyai Ambientum, 2016)
For the field of environmental pollution as for the sustainability field there is a need to have direct access not only to specific methodologies by a systematic approach, but also to assessment methods. In the mentioned fields, the difficulty is represented by the fact that sometimes it is difficult to establish limit values. Regarding sustainable development, there is often the situation of not having limit values, in contradiction to the environmental pollution field, where emission or immision limit values have already been established for most of the pollutants. Establishing development limit values is pretty difficult in all sustainability fields, i.e. economic, environmental and social fields. In the environmental field in most of the cases, there are limit values, but in the other two relevant sustainability fields, economic and social field, establishing limit values is not at all easy. This means that nowadays it is pretty difficult to precociously assess if a certain development will assure the sustainability of the region in consideration. In the last few years, several discussions were initiated on a scientific level, regarding the necessity to develop a so-called dynamic assessment methods, in order to make evaluation in those fields where limit values for a certain development cannot be defined or do not exist, as for instance in medical or social fields. The idea behind dynamic assessment methods is actually that different parameter gradients are compared, and not the parameter values themselves. Results will be debated and conclusions concerning the presented methodology will be drawn.